Penyelenggaraan Pendidikan Karakter Melalui Optimalisasi Pelaksanaan Kurikulum Tingkat Satuan Pendidikan - Herry Widyastono (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2010)
A huge number of research findings indicate that there is an obvious moral degradation within youngsters. This is one of the problems encountered by Indonesia. Corruption, intolerance, distrust, violence to other people, and so on and so forth are also other serious problems. Accordingly, the implant of a character building to learners constitutes a compulsory because this will not only result in smart students, but also make them to have good character as well a to be polite. By having such characters they will be useful for themselves of their lives and other people in community as well. The predetermined characters have already been included in the â€œgraduate competence standardâ€ and â€œcontent standardâ€ for basic and secondary education and these are as reference to enact school-based curriculum. There are some principles of conveying the values to students at primary, junior and senior secondary schools, among other things (a) sustainability, (b) be integrated to all existing subject matters, local content, self-development, and the habitual acts in schools, (3) the values are not taught in isolation, but be developed and be implemented involving students to be active and enjoyable.Â ABSTRAKBerbagai hasil penelitian menunjukkan terdapat kecenderungan semakin merosotnya nilai nilai moral dan karakter para remaja. Bahkan, tidak di kalangan remaja saja, secara umum bangsa Indonesia dihadapkan pada berbagai problem kebangsaan yang tidak mencerminkan karakter bangs Indonesia, seperti budaya korup, lebih menyukai jalan pintas, intoleran, kekerasan, ketidakpercayaan kepada pihak lain (distrust). Penyelenggaraan pendidikan karakter menjadi suatu keharusan karena pendidikan karakter tidak hanya menjadikan peserta didik menjadi cerdas, tetapi juga mempunyai budi pekerti dan sopan santun, sehingga keberadaannya sebagai anggota masyarakat menjadi bermakna baik bagi dirinya maupun bagi orang lain. Nilai-nilai karakter sudah termuat dalam Standar Kompetensi Lulusan dan Standar Isi yang merupakan acuan dalam menyusun Kurikulum Tingkat Satuan Pendidikan. Implementasi pendidikan karakter mengacu pada prinsip-prinsip: a) berkelanjutan; b) diintegrasikan ke dalam semua mata pelajaran yang sudah ada, muatan lokal, pengembangan diri, dan budaya sekolah, dan c) nilai-nilai karakter tidak diajarkan tapi dikembangkan dan dilaksanakan, serta d) pembelajaran dilakukan peserta didik secara aktif dan menyenangkan.